2016
DOI: 10.3762/bjnano.7.155
|View full text |Cite
|
Sign up to set email alerts
|

Nano- and microstructured materials for in vitro studies of the physiology of vascular cells

Abstract: The extracellular environment of vascular cells in vivo is complex in its chemical composition, physical properties, and architecture. Consequently, it has been a great challenge to study vascular cell responses in vitro, either to understand their interaction with their native environment or to investigate their interaction with artificial structures such as implant surfaces. New procedures and techniques from materials science to fabricate bio-scaffolds and surfaces have enabled novel studies of vascular cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 275 publications
(358 reference statements)
0
39
0
1
Order By: Relevance
“…Cells are generally capable of being oriented and directed, both in vivo and in vitro, by the micro-and nanotopography of their substrate in a complex feedback process known as contact guidance. [1][2][3][4][5] This phenomenon has been observed in a wide variety of settings, including organ and tissue generation and regeneration, 6 wound healing, 7,8 and axon pathfinding. 9,10 Contact guidance is also an important parameter in the design of medical implant surfaces, as tailored topography can provide a level of cellular control in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Cells are generally capable of being oriented and directed, both in vivo and in vitro, by the micro-and nanotopography of their substrate in a complex feedback process known as contact guidance. [1][2][3][4][5] This phenomenon has been observed in a wide variety of settings, including organ and tissue generation and regeneration, 6 wound healing, 7,8 and axon pathfinding. 9,10 Contact guidance is also an important parameter in the design of medical implant surfaces, as tailored topography can provide a level of cellular control in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Micro- and nanostructured materials for medical devices have demonstrated that surface topography as well as surface chemistry influence cellular behaviour such as adhesion, migration and proliferation [16]. It is important to understand and control cell behaviour by topography in order to modulate the functions of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Among the factors known to control cellular events, nano-topographical features play a pivotal role by exerting direct cueing on adherent cells. 2,9,10,[12][13][14][15][16][17] Based on this evidence, much effort has been invested in the design of synthetic nanostructured substrates to support the investigation of the interplay between nanotopographical cues and cellular functions. 2,10,12,13,15,18 Among the panoply of techniques developed to nanostructure biomaterials, anodization has rapidly emerged as a simple but effective electrochemical treatment to create bioactive nanostructures composed of arrays of aligned nanotubes on titanium, the gold standard in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…2,9,10,[12][13][14][15][16][17] Based on this evidence, much effort has been invested in the design of synthetic nanostructured substrates to support the investigation of the interplay between nanotopographical cues and cellular functions. 2,10,12,13,15,18 Among the panoply of techniques developed to nanostructure biomaterials, anodization has rapidly emerged as a simple but effective electrochemical treatment to create bioactive nanostructures composed of arrays of aligned nanotubes on titanium, the gold standard in medicine. [18][19][20][21] The design of morphological parameters, mainly nanotube diameter, has been achieved through the modulation of experimental parameters (i.e., anodization voltage and time, composition of the electrolytic solution), permitting to rationally engineer nanotopographical features and assess their influence on cellular events.…”
Section: Introductionmentioning
confidence: 99%